Are public administrations the only ones responsible for organizing the administration of green spaces within the localities? An assessment of the perception of the citizens of Constanta municipality in the context of sustainable development - Stan, Mari-Isabella (Technium Social Sciences Journal, 2022)
The sustainable management of green spaces in urban localities is a major challenge for Romania's big cities. In terms of urban development, local public administrations are developing guidance and regulatory documents, one of the key elements of urban planning being the green urban infrastructure. Thus, the local public administration authorities have the obligation to keep track of the green spaces on the territory of administrative units by establishing local registers of the green spaces within the built-up areas of the localities, which must be correlated with the provisions of general urban plans and drafted urban planning regulations. The aim of this article is to capture the citizens’ perception of the manner in which the local public administration is preoccupied with the sustainable management of green spaces, in a context in which the legal provisions related to ensuring a green space area per capita are not complied with. Even though local public administration authorities are responsible for the sustainability measures in urban areas, given that the existence of green spaces is one of the important factors which define the quality of life, the involvement and participation of the community, of each citizen, as well as of all the entities present in this space is necessary.